2017
DOI: 10.1101/126995
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gut microbiota composition related withClostridium difficile-positive diarrhea andC. difficiletype (A+B+, A-B+, and A-B-) in ICU hospitalized patients

Abstract: 16

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The correlation network analysis revealed a significant positive correlation between Lachnoclostridium and IL-1β [50]. In addition, Parabacteroides is associated with Clostridium difficile-positive diarrhea and CD [51,52]. A previous study found that the intestinal microorganisms of young animals were still in the “window stage” during the early weaned stage, and that changes in intestinal microorganisms during this period will increase the susceptibility to diseases at later ages [53].…”
Section: Discussionmentioning
confidence: 99%
“…The correlation network analysis revealed a significant positive correlation between Lachnoclostridium and IL-1β [50]. In addition, Parabacteroides is associated with Clostridium difficile-positive diarrhea and CD [51,52]. A previous study found that the intestinal microorganisms of young animals were still in the “window stage” during the early weaned stage, and that changes in intestinal microorganisms during this period will increase the susceptibility to diseases at later ages [53].…”
Section: Discussionmentioning
confidence: 99%